HISTORY OF THE DEVELOPMENT OF THE CONCEPT OF MEDIA ETHICS AND ITS IMPACT ON THE DEVELOPMENT OF SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the topic of media ethics, which is considered an important factor in the development of society. Moral principles, ethics and norms play an important role in controlling personal and public influence in the media and social networks. Its importance has been demonstrated in protecting against fake news, preserving authentic information, protecting human rights and strengthening democratic society. The conclusion is that research and knowledge on this topic not only have contemporary significance for society, but also provide great assistance in finding answers to global issues.